Levantamento florístico das espécies utilizadas na arborização urbana de Cuiabá, Mato Grosso, Brasil - Gomes, Edinalda Milioranza (2023)
The urbanization process is growing and global, which intensifies the transformation of the landscape through human actions. Cities are often considered ecologically uninteresting environments, but urban areas can be very rich in biodiversity. The present work sought to carry out a floristic survey of the species produced and destined for public roads, to compare with the species present in the central beds of two avenues and two neighborhoods of Cuiabá, Mato Grosso, as well as to verify the current legislation on afforestation in the urban perimeter of the County. We also propose a list of regional flora species suitable for the school space as a subsidy for Environmental Education. In the first chapter, to determine the differences in seedling production according to the origin (native or exotic), we built general linearized models (GLM, glm function, stats package, R Core Team 2022). For abundance analyses, we built abundance curves – “rank-abundance” or also Whittaker plot. In Horto, there was no significant mean difference in production between native and exotic species. Comparing afforestation between neighborhoods, it is demonstrated that in both there was a higher occurrence of exotic species. Among the avenues, there was less diversity of species compared to the neighborhoods. However, little diversity was found in both sites. In the second chapter, to define criteria and recommend species, the following parameters were investigated: landscape potential, size, habit, ecological information, phenology and toxicity. The result of the survey made it possible to suggest 32 species of the regional flora belonging to 27 genera and 18 families of angiosperms that can be used in the school space. Urban forestry is an essential component of sustainable urban development, contributing to a healthier, more resilient and livable environment for all.